Effects of weight loss intervention on body composition and blood pressure among overweight and obese women: findings from the MyBFF@home study - Mansor Fazliana; Ahmad Zamri Liyana; Azahadi Omar; Rashidah Ambak; Noor Safiza Mohamad Nor; Ummi Kalthom Shamsudin; Narul Aida Salleh; Tahir Aris (BMC, 2018)
Abstract Background Obesity is related to the increased incidence of hypertension and in healthy individuals, blood pressure changes with age and body mass. The aims of this paper were to evaluate the effectiveness of the weight loss intervention on body composition and blood pressure, and to evaluate the relationship between these factors among housewives in the MyBFF@home study. Methods MyBFF@home intervention was a quasi-experimental study which involved 328 overweight and obese housewives aged 18-59 years old (Control group: 159, Intervention group: 169). Data of the control and intervention group (pre and post intervention who completed the body composition and blood pressure measurements were analysed. Body compositions were measured using the Body Impedance Analyser (InBody 720) and blood pressure (Systolic and Diastolic) was taken using the blood pressure monitoring device (Omron HEM 907) at baseline, 6 month and 12 month. Data analyses (Pearson's correlation test and ANOVA) were performed and analysed using SPSS Statistics for Windows, version 22.0. Results Visceral fat area, fat mass and body fat percentage, were all significantly decreased in the intervention group compared to the control group after 6 month intervention (p < 0.05). Systolic blood pressure was reduced significantly by − 6.81 mmHg (95% CI: -9.72,-3.90; p < 0.01) in the intervention and by − 7.95 mmHg (95% CI: -11.69,-4.20; p < 0.01) in the control group after 6 month intervention. Diastolic blood pressure was significantly correlated with BMI (r = 0.19), waist circumference (r = 0.23), body fat mass (r = 0.22), body fat percentage (r = 0.18) visceral fat area (r = 0.22) and skeletal muscle mass (r = 0.14) with p < 0.05. At 12-month follow-up, no significant changes of blood pressure were detected in both groups. Conclusion There were significant changes in the body fat and systolic blood pressure over 6 month among the participants in the intervention group compared to the control group. However, both groups were unable to sustain the positive changes in the body fats during the maintenance phase. There was a relationship between the body composition and blood pressure during the weight loss intervention and weight loss maintenance phase. Participation among obese housewives in a community-based intervention programme led to the improvements in blood pressure and body composition.